(untitled) (LIS TODAY, 2022)
We are living in the virtual environment and the emerging growth and developments of internet has modified our society in every aspect. Libraries are more responsive in making users net-savvy. Not only have internet and technological developments affected the formats and sources of information, but also how and where libraries provide their services to the user. The World Wide Web (WWW) and Internet’s emergence as a new medium for information storage and transmission have created an unrivalled medium for delivering information with higher speed and efficiency. All India Institute of Medical Sciences (AIIMS) are autonomous, government-funded, public medical institutions established for the advancement of medical education in India. The paper examines what web-based services, why they are important, and why they are so popular among users , as well as their benefits and drawbacks in AIIMS library, and on the basis of their website details, the evaluation of four AIIMS libraries is also emphasized.